Spatial dimension of social exclusion of urban poor in traditional core areas of Ilorin, Nigeria. Issue 1 (2nd January 2021) - Bako, A.I.; Aduloju, O. T. B.; Anofi, A. O.; Otokiti, K. V.
ABSTRACT: This study assesses the spatial dimensions of social exclusion in the traditional core areas of Ilorin with specific emphases on the urban poor in Ilorin. For methodology, data collection instruments used include questionnaire administration, oral interview, personal observation for primary data; journals, reports for secondary data, respectively. The findings among others reveal that Agbarigidoma, Abimbola, Anifowose and Sheik Abdulquadri sectors in Oloje; as well as Abayawo, Kongbari, Sarumi and Sefura in Okelele were excluded from urban processes and operations based on a low income, poor housing condition, unemployment and lack of essential services. Furthermore, this study reveals that the study area is running at the risk of poor environmental sanitation, inadequate infrastructure and environmental degradation. Policy responses like proper budgetary allocation, citizen participation toward protecting human rights and strategies like the bottom-up approach were recommended as a way forward in coping and forestalling exclusion.